Phase I/II trial of intracerebral transplantation of autologous bone marrow stem cells combined with recombinant peptide scaffold for patients with chronic intracerebral haemorrhage: a study protocol - Arisa Miura; Yoichi M Ito; Masahito Kawabori; Miki Fujimura; Kaoru Kahata; Hideo Shichinohe; Kenichiro Maeda; Masahiko Mukaino; Ryo Kogawa; Kentaro Nakamura; Shuho Gotoh; Kota Kurisu (BMJ Open)
Introduction Intracerebral haemorrhage (ICH) stands as a leading global cause of death and disability, posing a significant challenge with limited treatment options, especially for chronic patients. Recent advances in stem cell therapies have opened new avenues for therapeutic potential. Our previous preclinical research has demonstrated that intracerebral transplantation of bone marrow stromal cells (BMSCs) combined with a recombinant human collagen type I scaffold enables higher cell survival and engraftment and holds promising potential. In this article, we present the protocol for a novel clinical trial, named ‘Research on Advanced Intervention using Novel Bone MarrOW stem cells for chronic intracerebral haemorrhage’ (RAINBOW-Hx).Methods and analysis RAINBOW-Hx is a phase I/II, open-label, uncontrolled study with the primary objective of assessing the safety and efficacy of intracerebral transplantation of autologous BMSCs combined with the scaffold (HUFF-01) in patients with chronic ICH. Eight patients, experiencing moderate to severe neurological deficits for 12 months or longer, will be enrolled. The haemorrhage location will be limited to the basal ganglia and thalamus. Approximately 50 mL of bone marrow will be extracted from the iliac bone of each patient, and BMSCs will be cultured using autologous platelet lysate. 3 days before transplantation, BMSCs will be combined with the scaffold to generate HUFF-01. Each patient will receive a 50 000 HUFF-01 dose, containing approximately 50 million BMSCs, through stereotactic transplantation into the haemorrhagic cavity. Neurological assessments, MRI, 18F-fluorodeoxyglucose positron emission tomography and 123I-Iomazenil single-photon emission CT will be performed for 1 year after administration.Ethics and dissemination The trial protocols were reviewed and approved by the Institutional Review Board of the Hokkaido University Hospital (R5-11), and this study is conducted according to Good Clinical Practice guidelines and the principles of the Declaration of Helsinki. The results of this trial will be submitted for publication in a peer-reviewed scientific journal.Trial registration number jRCT2013230053, Japan Registry of Clinical Trials.